2015
DOI: 10.1123/jpah.2013-0442
|View full text |Cite
|
Sign up to set email alerts
|

Affective Response to Exercise and Preferred Exercise Intensity Among Adolescents

Abstract: Background Little information exists as to the exercise intensity that adolescents enjoy and whether identifiable subgroups of adolescents will choose higher-intensity exercise. Methods Healthy adolescents (N = 74; mean age = 11.09) completed a cardiorespiratory fitness test, a moderate-intensity exercise task, and an exercise task at an intensity that felt “good”. Heart rate (HR), work rate (WR) and ratings of perceived exertion (RPE) were assessed every 3 minutes. Results During the “feels good” task, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Present results also lend support to the implementation of affect-regulated exercise, which has been cited as a viable way in which to minimise feelings of displeasure during exercise (Parfitt, Alrumh, & Rowlands, 2012). Recent evidence has demonstrated that exercising at an intensity that feels 'good' leads to a meaningful intensity for cardiovascular benefits (Schneider & Schmalbach, 2015) across active (Hutchinson et al, 2018) and sedentary populations (Hamlyn-Williams, Tempest, Coombs, & Parfitt, 2015). Affect-regulated exercise offers an easily implementable way for individuals to regulate their exercise intensity per their individual preference while ensuring a pleasant experience.…”
Section: Preference For Exercise Intensitysupporting
confidence: 72%
“…Present results also lend support to the implementation of affect-regulated exercise, which has been cited as a viable way in which to minimise feelings of displeasure during exercise (Parfitt, Alrumh, & Rowlands, 2012). Recent evidence has demonstrated that exercising at an intensity that feels 'good' leads to a meaningful intensity for cardiovascular benefits (Schneider & Schmalbach, 2015) across active (Hutchinson et al, 2018) and sedentary populations (Hamlyn-Williams, Tempest, Coombs, & Parfitt, 2015). Affect-regulated exercise offers an easily implementable way for individuals to regulate their exercise intensity per their individual preference while ensuring a pleasant experience.…”
Section: Preference For Exercise Intensitysupporting
confidence: 72%
“…Affect-regulated exercise offers an easily implementable way for individuals to regulate their exercise intensity while ensuring a pleasant experience. Preliminary evidence has demonstrated that exercising at an intensity that feels 'good' leads to a meaningful intensity for cardiovascular benefits and is a strategy that can be implemented by sedentary adults in ecologically valid settings (Hamlyn- Williams, Tempest, Coombs, & Parfitt, 2015) and by adolescents (Schneider & Schmalbach, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The method used in this study to gauge individuals’ affective response to moderate-intensity exercise has been used previously in our lab and has shown evidence of external validity among older adolescents; more positive affective responses were positively correlated with average daily time spent in MVPA as measured by accelerometry ( Schneider et al, 2009 ). Data from a subset of participants in the present study sample provided further evidence of external validity in that affective responses were predictive of chosen work-rate on the “feels good” task but not predictive of Ratings of Perceived Exertion ( Schneider and Schmalbach, 2014 ). Evidence for the substantive validity of the assessment within the present study sample includes a Cronbach’s alpha of 0.97 across the individual ratings of the Feeling Scale every 3 min and a positive correlation between the summary affective response score and a Feeling Scale rating provided immediately upon the conclusion of the cardiorespiratory fitness test ( r = 0.63, p < 0.001).…”
Section: Methodsmentioning
confidence: 69%